2018
DOI: 10.30674/scripta.70070
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the modern nation state in the Anthropocene

Abstract: This article presents the nature of conflicts in postcolonial societies as the consequence of being under external control and economic exploitation. Drawing on empirical cases from Indonesia and a comparative literature review of African states, this article reveals a huge dilemma within the desire to build a solid nation state in a deeply pluralistic society. The nature of the modern nation state, which from the start requires the forcible subjugation of the population, has become one of the greatest paradox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This would facilitate a Dar al-Islam-focused environmental governance for the Ummah within minimal state frameworks. Furthermore, as mentioned earlier, I argue that Islamic governance should be organized organically around the center of God's sovereignty (Alkatiri 2018a). Perhaps fortuitously, my proposed model resonates with one proposed by Seyyed Hossein Nasr: one can envisage the possibility of the rise, once again, of a trend in the future towards a kind of Islamic political thought which combines the ideal of the unity of the Islamic world, based on culture, Divine Law, intellectual life, etc., with separate political units which embrace the majority peoples and cultural zones of the Islamic world, such as the Arabic, the Persians, the Turkish, etc… (Nasr 1994: 313) Such a project of 'the unity of Islam as a world civilization' certainly depends on creative interpretations of Shariah.…”
Section: Cut the Vicious Circle Let The Muslims Free To Heed The Call...mentioning
confidence: 85%
See 4 more Smart Citations
“…This would facilitate a Dar al-Islam-focused environmental governance for the Ummah within minimal state frameworks. Furthermore, as mentioned earlier, I argue that Islamic governance should be organized organically around the center of God's sovereignty (Alkatiri 2018a). Perhaps fortuitously, my proposed model resonates with one proposed by Seyyed Hossein Nasr: one can envisage the possibility of the rise, once again, of a trend in the future towards a kind of Islamic political thought which combines the ideal of the unity of the Islamic world, based on culture, Divine Law, intellectual life, etc., with separate political units which embrace the majority peoples and cultural zones of the Islamic world, such as the Arabic, the Persians, the Turkish, etc… (Nasr 1994: 313) Such a project of 'the unity of Islam as a world civilization' certainly depends on creative interpretations of Shariah.…”
Section: Cut the Vicious Circle Let The Muslims Free To Heed The Call...mentioning
confidence: 85%
“…My PhD research assessed the willingness, ability, and possibility of local Muslim communities in Indonesia (as the world's largest Muslim nation) to pursue the ideals and actions of relocalization (Alkatiri 2015). I found that two local communities-namely, Hidayatullah in Balikpapan, East Kalimantan (Alkatiri 2018a), and An-Nadzir in Gowa, South Sulawesi-provide the closest example of intentional communities which can be transformed into models of endogenous 7 Islamic relocalization.…”
Section: Turning Ideas Into Actionmentioning
confidence: 99%
See 3 more Smart Citations